Edukasi Upaya Mencegah Kejadian Nyeri Neuropati Diabetik Pada Pasien Diabetes Mellitus Tipe 2 Dengan Dislipidemia di Puskesmas Trowulan Kabupaten Mojokerto - I Made Subhawa Harsa; Andiani Andiani; Harsono Wiradinata; Sulistiawati Sulistiawati; Ni Putu Chintya Eka Shanty; Viky Nauvalia Zahiroh (Indonesian Journal Publisher, 2024)
Diabetes mellitus can lead to dyslipidemia, which can increase the risk of vascular obstruction or atherosclerosis. The occurrence of dyslipidemia in people with diabetes mellitus can trigger diabetic neuropathic pain (DNP). Diabetes mellitus with complications of diabetic neuropathic pain became the top 5 disease of the Prolanis program in Puskesmas Trowulan, Mojokerto. DNP is difficult to treat and severely interferes with the quality of the daily lives of patients. The purpose of this Public Service (Pengmas) is to increase public knowledge and understanding of efforts to prevent the occurrence of diabetic neuropathy pain in patients with type 2 diabetes mellitus with dyslipidemia in the Puskesmas Trowulan, Mojokerto. The method used in this activity is carried out in three stages: planning, implementation, evaluation, and follow-up. The results of this activity showed that the average pre- and post-test scores increased significantly before and after education, which is 0.94. This indicates that the public has understood the material submitted in connection with efforts to prevent an increase in the incidence of type 2 diabetes mellitus, dyslipidemia, and diabetic neuropathic pain in the Puskesmas Trowulan, Mojokerto.